2016
DOI: 10.1590/s1518-8787.2016050005832
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural adaptation of the General Functioning Scale of the Family

Abstract: OBJECTIVE To describe the process of cross-cultural adaptation of the General Functioning Scale of the Family, a subscale of the McMaster Family Assessment Device, for the Brazilian population.METHODS The General Functioning Scale of the Family was translated into Portuguese and administered to 500 guardians of children in the second grade of elementary school in public schools of Sao Gonçalo, Rio de Janeiro, Southeastern Brazil. The types of equivalences investigated were: conceptual and of items, semantic, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
1
15
0
4
Order By: Relevance
“…The reliability of the Malay GF12 was tested in terms of internal consistency and test-retest reliability whereby ndings were in agreement with the Spanish and French FAD-GF12 studies 34,35 . The Cronbach alpha of the Malay GF12 was 0.89 which indicates a high level of internal consistency supporting the previous ndings of Spanish and Dutch versions 20,36 .…”
Section: Discussionmentioning
confidence: 59%
“…The reliability of the Malay GF12 was tested in terms of internal consistency and test-retest reliability whereby ndings were in agreement with the Spanish and French FAD-GF12 studies 34,35 . The Cronbach alpha of the Malay GF12 was 0.89 which indicates a high level of internal consistency supporting the previous ndings of Spanish and Dutch versions 20,36 .…”
Section: Discussionmentioning
confidence: 59%
“…In the scale adapted for patients with heart failure, "algodão" (cotton) was replaced with "lixa" (sandpaper), 19 a more adequate term in Portuguese to express a sensation of roughness rather than dryness. 24 In the Turkish adaptation, the term "cotton" was suppressed and the item read "my mouth gets really dry when I am thirsty." 18 Item 5 remained unchanged in our and other adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…The study included 126 patients, a sample size characteristically seen in validation studies. [23][24][25][26] Data collection took place in the morning, afternoon, and evening shifts during HD sessions. The questionnaire included identification information and probed into etiology of CKD, time on HD, KT/V (a marker of quality of dialysis), comorbidities, body mass index (BMI), interdialytic weight gain (an indicator of fluid status), biochemical tests (transferrin, hemoglobin, ferritin, albumin, creatinine, pre-dialysis blood urea nitrogen, post-dialysis blood urea nitrogen).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to consider this study as a possible solution or at least a proposal to be taken into account in further studies about the cross-cultural adaptation of the assessment tool to the Brazilian reality. In this context, Pires et al 23 have indicated another Brazilian version of FAD, which they stated revealed a good applicability, easy understanding by the population, and good measurement of the construct of interest.…”
Section: Discussionmentioning
confidence: 99%